Revealing the dual role of nanoparticle size and surface ligands in plasmon-enhanced photocatalysis of Au/TiO2 nanorods - Slapničar, Špela; Caf, Maja; Kralj, Slavko; Žerjav, Gregor; Pintar, Albin (Applied surface science, 2026)
[Display omitted] •Au/TiO2 photocatalysts were prepared from Na-citrate stabilized Au suspensions.•Au nanoparticles suppress electron–hole recombination and extend carrier lifetime.•Smaller Au nanoparticles act as efficient charge separation and transfer sites.•Activity of Au/TiO2 materials depends on the number of deposited Au nanoparticles.•Residues of Na-citrate on the catalyst surface affect the Au/TiO2 activity. The development of plasmon-enhanced TiO2 photocatalysts offers exciting opportunities for the use of visible light in environmental and energy-related applications. A key parameter that determines their performance is the size and distribution of the plasmonic metal nanoparticles (NPs), which strongly influence charge separation, light absorption and interfacial chemistry. In this work, we have systematically investigated the role of Au NPs size on the structural, electronic and photocatalytic properties of hydrothermally synthesized TiO2 nanorods (TNR). Au NPs with well-controlled diameters in the range of 10–50 nm were uniformly deposited on the TNR surfaces, which was confirmed by electron microscopy and elemental mapping. UV–Vis diffuse reflectance spectra confirmed the absorption of localized surface plasmon resonance (LSPR) in the visible region, with peak positions depending on both the size of the NPs and the presence of Na-citrate residues from the synthesis. Supplementary spectroscopic analyses showed that citrate residues altered the surface chemistry, impaired charge transfer and partially blocked active sites. Photoluminescence and time-correlated single photon counting measurements revealed that Au decoration effectively suppressed the recombination of electrons and holes and prolonged the lifetime of charge carriers, while electron paramagnetic resonance spectroscopy showed improved stabilization of Ti3+ centers and oxygen vacancies upon visible-light irradiation. Photocatalytic tests, evaluated by the generation of reactive oxygen species and the degradation of bisphenol A (BPA), showed that the activity increased with decreasing NPs size. The sample with the smallest Au NPs showed the highest reactivity and achieved a BPA degradation of ∼40 within 4 h. Thus, it clearly outperformed both the larger Au-decorated TNR and the untreated TNR reference sample. Nevertheless, residual citrate limited the overall efficiency by hindering charge transport and surface reactivity. These findings provide a pathway for the rational design of more efficient plasmonic photocatalysts by controlling NP size and removing synthesis by-products.